Increasing retail sales of healthy foods in Ethiopia: Lessons from MSME surveys in two urban areas - de Brauw, Alan; Hirvonen, Kalle; Mekonnen, Daniel Ayalew (International Food Policy Research Institute, 2024)
The food environment represents the place in which demand for food meets supply—consumers purchase foods in the food environment, while retailers of the food consumers purchase represent the end of the value chain. In many countries, the food environment is characterized by a large number of micro-, small-, and medium-sized enterprises (MSMEs) who sell the majority of healthy foods. Ethiopia fits this description; among healthy food groups purchased by at least one-third of customers within a given week, at least 88 percent of consumers making purchases by them from MSMEs (de Brauw and Hirvonen 2024).